Diabetic nephropathy: Pathophysiology and potential therapeutic role of plant extracts - Mehak Naseer Mir; Ishfaq Ahmad Malik; Rayees Ahmad Naik; Sonalika Singh; Aabid Rashid Hurra; Zahid Ahmad Wani; Rakhmat Shah; Yaqoob Lone (Endocrine and Metabolic Science)
Objective: This review aims to explore the molecular mechanisms underlying diabetic nephropathy (DN), with a particular focus on the role of oxidative stress. Additionally, it evaluates the therapeutic potential of plant-based extracts rich in bioactive compounds for the management of diabetes and its associated renal complications. Results: Oxidative stress is identified as a key contributor to DN pathogenesis. Several major pathways are involved, including hypoxia-inducible factor-1 (HIF-1), transforming growth factor-beta (TGF-β), mitochondrial dysfunction, renin-angiotensin-aldosterone system (RAAS) activation, and endothelial nitric oxide synthase (eNOS) uncoupling. These mechanisms collectively lead to podocyte injury, tubular damage, extracellular matrix accumulation, disrupted renal hemodynamics, and glomerular hyperfiltration. Plant-derived compounds have shown potential in modulating these pathways, thereby offering renal protective effects. Conclusion: Plant-based remedies enriched with bioactive compounds represent promising adjunct therapies for managing diabetes and its renal complications. Their integration into conventional treatment regimens may provide a holistic approach to glycemic control and reduction of oxidative stress-induced kidney damage. This review underscores the importance of multifaceted therapeutic strategies targeting both metabolic dysregulation and oxidative stress to effectively prevent and manage diabetic nephropathy.